HARMONIZATION OF INDUSTRIAL AND TRADE POLICY OF THE ENTERPRISE - K. Barmashov (Вестник университета, 2018)
Methodological and methodical questions of denition of a concept of harmonization in economy and estimates of harmonization of social and economic system functioning, concretized on the example of harmonization of industrial and trade policy of the industrial enterprise are considered. The research of questions of harmony in economy opens the existing antagonistic contradictions in external and internal environments of activity of participants of the economic relations. Harmonization of industrial and trade policy of the enterprise is, on the one hand, the strategic plan of production and sales, and on the other hand, process of coordination of purposes, principles, methods, criteria and indicators of the production, marketing and business processes providing them at all stages of life cycle of policy which leads to decrease of economic damage